2017
DOI: 10.1038/s41598-017-07780-x
|View full text |Cite
|
Sign up to set email alerts
|

Possible involvement of the oxLDL/LOX-1 system in the pathogenesis and progression of human intervertebral disc degeneration or herniation

Abstract: Epidemiological studies have concluded that hyperlipidemia and atherosclerosis were related to intervertebral disc degeneration (IVDD). The presence of oxidized low density lipoprotein (ox-LDL) and the expression of lectin-like oxidized low density lipoprotein receptor 1 (LOX-1) have not been explored in this tissue. In this study, we investigated the presence of ox-LDL and the expression of its receptor LOX-1 in non-degenerated, degenerated or herniated human intervertebral discs (IVDs). The expression of LOX… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 49 publications
2
19
0
Order By: Relevance
“…, as well as scavenger receptors (SRs) ( 57 ). Similar sets of PRRs have been reported to modulate bone metabolism ( 58 61 ).…”
Section: Cells Of the Myeloid Lineagesupporting
confidence: 72%
“…, as well as scavenger receptors (SRs) ( 57 ). Similar sets of PRRs have been reported to modulate bone metabolism ( 58 61 ).…”
Section: Cells Of the Myeloid Lineagesupporting
confidence: 72%
“…Thirdly, the oxidized low-density lipoprotein (oxLDL) and the increased expression of lectin-like oxidized low-density lipoprotein receptor 1 (LOX-1) that are caused by dyslipidaemia may also be involved in the development of symptomatic IDH. Our previous study suggested [44] that the levels of the oxLDL and LOX-1 were positively correlated with the extent of IDH. The mechanism of action involved the increase in the expression of MMP3 that was induced by LOX-1.…”
Section: Discussionmentioning
confidence: 92%
“…oxLDL has been detected in human IVD tissues, and compared with normal disc tissues, the proportion of oxLDL was significantly higher in degenerated discs. More importantly, the mean percentage of oxLDL‐positive‐immunostained cells in the AF was higher than that in the NP 17 . The AF seems, therefore, to be more susceptible to oxLDL.…”
Section: Introductionmentioning
confidence: 84%